(untitled) (The Agriculturists, 2015)
Long-term tea cultivation has led to degradation of the soil. Old tea soils require rehabilitation for restoring soil health. Soil rehabilitation by growing different green crops can break the chain of monoculture of tea. An experiment was conducted at The Bangladesh Tea Research Institute (BTRI) Farm during 2008-2011 to find out the efficiency of different green crops on the improvement of soil properties. Four green crops such as Guatemala, Citronella, Mimosa and Calopogonium were grown to develop the nutritional value of the degraded tea soil. Soil samples were collected and analyzed before and at the end of experiment. Soil pH was increased in all four green crops treated plots with the highest increase in Citronella treated plots (from 4.1 to 4.5). Highest content of organic carbon (1.19%) and total nitrogen (0.119%) were found in Mimosa and Calopogonium treated plots, respectively. Concentration of available phosphorus, calcium and magnesium in all green crops treated plots were above the critical values, while available potassium content was above the critical value in Guatemala, Citronella and Mimosa treated plots. Changes in soil pH and available potassium were significant, while changes in organic carbon content, total nitrogen and available calcium were insignificant. Changes in available phosphorus and magnesium were significant. The Agriculturists 2014; 12(2) 34-38